Pricing for differentiated internet services - Gong, Zheng. (2008)
This dissertation starts form the study and survey of the Differentiated Services (DiffServ) architecture and currently existing pricing models. DiffServ provides a feasible QoS solution for the Internet, where scalability is achieved by offering services on aggregate rather than per-flow basis and forcing as much as possible the per-flow states to the edges of the network.